The influence of investment risk, influencers, and return perception on Gen Z interest - Gara, Made Adhika Laksamana (Universitas Pendidikan Nasional, 2025)
This research aims to the investment interest of Generation Z is considered essential because the current challenges for Generation Z relate to financial issues. Generation Z tends to spend their money on new experiences rather than saving for long-term needs. This research aims to examine the influence of Investment Risk, Social Media Influencers, and Return Perception on the investment interest of Generation Z in Denpasar city using the Bibit application. The data analysis technique employed in this study utilizes IBM SPSS Statistics 23 software. The research was conducted in Denpasar city, and data was collected through questionnaires distributed to 170 respondents who were familiar with or had used the Bibit application. The research results indicate an influence of Investment Risk, Social Media Influencers, and Return Perception on investment interest, as confirmed by the hypothesis testing: 1) Investment Risk has a positive and significant impact on Investment Interest, 2) Social Media Influencers have a positive and significant impact on Investment Interest, and 3) Return Perception has a positive and significant impact on Investment Interest.